Ladies in hating : a novel - Vasti, Alexandra (St. Martin's Griffin, 2025)
"Celebrated authoress Lady Georgiana Cleeve has achieved fame and fortune. Unfortunately, she's also acquired an enemy: the enigmatic Lady Darling, whose spine-tingling plots appear to be pulled straight from Georgiana's own manuscripts. What's a stubborn, steely writer to do? Unmask her rival, of course. But unmasking doesn't go according to plan--because Lady Darling is actually Cat Lacey, the butler's daughter and object of Georgiana's very secret, very embarrassing teenage infatuation. Cat Lacey has spent a decade clawing her family out of poverty. The last thing she needs is to be distracted by the stunning(ly pretentious) Lady Georgiana Cleeve. But Cat can't seem to escape her infuriatingly beautiful rival--including at the eeriemanor where they both plan to set their next books. The plot unexpectedly thickens, however, when the novelists find themselves trapped in the manor together. In between ghostly moans and spectral staff, Cat and Georgiana come face-to-face with real danger: the scorching passion that's been haunting their rivalry all along"--